الثورة الليبية والمحكمة الجنائية الدولية - سوداني, نورالدين (جامعة الوادي University of Eloued, 2018)
تعتبر الثورة الليبية اول ثورة شهدها العالم العربي في اطار ما يسمى بالربيع العربي التي انحرفت عن مسارها السلمي وتحولت الى نزاع مسلخ داخلي ادى الى مقتل الكثير من المدنيين، وارتكبت خلاله انتهاكات لحقوق الانسان، الامر الذي ادى الى تدخل المجتمع الدولي، وكان تدخل مجلس الامن من خلال اصداره لعديد القرارات الدولية، ولعل من اهمها القرار 1970 الذي احال بموجبه الوضع في ليبيا الى المحكمة الجنائية الدولية من اهم اوجه التدخل في النزاع،حيث جعله ياخذ طابعا جنائيا قضائياجنائيا دوليا ادى الى صدور عديد مذكرات القبض بحق كبار المسؤولين. The libyan révolution is the first révolution know to the Arab world in the from work of the so-called Arab spring which deviated from its peaceful course to internal armed conflict, led to killing many civilians and causing serious human rights violations, led to the intervention of internationale community, through the issuance of several intervention résolution, thé most important one is decision 1970 in which the situation of Libya was referred to the internationale criminalité Court, ans which was considered the most important aspects of the intervention in the conflict. which make it take an internationale criminal judicial character, les to the issuance of several arrest were issued against senior officiels
Keywords: خلفيات الثورة، التدخل الدولي، مذكرات القبض، شرعية التدخل